Comparison of Two Different Grafts in Nasal Framework Reconstruction of Binder Syndrome: Cartilage and Silicone. Issue 6 (September 2017) - Tian, Le; You, Jianjun; Wang, Huan; Zhang, Bo; Xu, Yihao; Lu, Xiaona; Fan, Fei
Abstract : Background: Binder syndrome is a rare congenital malformation with a flat facial profile especially a depressed nose. Rhinoplasty plays an important part in the multidisciplinary surgical protocol. Different materials have been proposed to reconstruct nasal framework. But fewer evidence concerns which graft can achieve more stable and appreciated nasal contour. In this article, the authors reported surgical details and experience of nasal framework reconstruction of Binder syndrome, compare the esthetic outcomes of 2 grafts: autologous costal cartilage and L-shaped silicone covered with auricular cartilage. Methods: A retrospective study of 25 Binder syndrome patients (9 with silicone and 16 with costal cartilage) was managed. Anthropometric method was used to evaluate nasal profiles preoperatively and postoperatively. Surgical techniques, complications were reviewed. Statistics analysis was managed. Probability ( P ) of <0.05 was considered significant. Results: Tip proportions (angle of convexity of the face with nose, nose tip–length quotient, tip projection anterior glabellar line quotient) improved in silicone group, but cartilage group achieved superior esthetic outcomes than silicone in tip projection, subnasal protrusion, and nasal labial angle. Conclusion: Autologous costal cartilage is more favorable to reconstruct the nasal framework and regain nasal esthetics of Binder syndrome.